Spatio-temporal changes of winter and spring phytoplankton blooms in Arabian sea during the period 1997–2020. (15th April 2023) - Anjaneyan, P.; Kuttippurath, J.; Hareesh Kumar, P.V.; Ali, S.M.; Raman, Mini
Abstract: Arabian Sea (AS) experiences Chlorophyll-a (Chl-a) blooms during winter and early spring (November–March) mainly due to the changes induced by seasonally reversing monsoon winds and associated processes. The seasonal blooms exhibit distinct regional patterns in their onset, duration, intensity and peak period. Recent changes in ocean dynamics and plankton composition have inflicted adverse effects in the distribution of Chl-a concentration in AS. Here, we analyse the long-term spatio-temporal changes in winter and early spring bloom events during the period 1997–2020, and evaluate the role of sea surface temperature (SST), mixed layer depth (MLD), sea surface salinity, winds, mesoscale eddies and surface currents on these bloom occurrences. We observe a significant reduction in these blooms, which started in the early 2000s and intensified in the last decade (2010–2020), with a notable drop in the adjacent gulfs (Gulf of Aden: 1.38 ± 0.7 × 10 −5  mg m −3 yr −1, Gulf of Oman: 4.71 ± 1.35 × 10 −6  mg m −3 yr −1 ) and West coast of India (−6.71 ± 2.85 × 10 −6  mg m −3 yr −1 ). The MLD and ocean temperature are the major factors that govern bloom in Gulf of Oman and open waters. Conversely, the coastal upwelling and eddies drive blooms in Gulf of Aden. The winter cooling trigger the bloom in the northern Indian west coast, but the inter-basin exchange of surface waters through the West Indian Coastal Current inhibits its southward spread. This study, therefore, reveals unique processes that initiate and control the winter and early spring blooms in different regions of AS. The ongoing warming of AS could contribute to further decline in these seasonal blooms, which would be a great concern for regional marine productivity and associated regional food security. Graphical abstract: Image 1 Highlights: Phytoplankton blooms in winter show distinct regional characteristics in Arabian Sea. Coastal upwelling and mesoscale eddies play a key role in blooms of the adjacent gulfs. Surface currents inhibit the plankton growth in the southern Arabian Sea. The winter-spring bloom shows negative trends in the gulfs and West coast India.